Vertical Blade Fiberglass Composite for Wind Turbine Power Plant Application - Shomad, M. Abdus; Ruddin Hidayat, Fahmi (Universitas Muhammadiyah Yogyakarta, 2021)
Wind is a renewable energy that is used for electrical energy in several countries. Indonesia is one of the countries that utilizes wind energy for electrical energy. The potential for wind in Indonesia is located in coastal areas. To apply the potential for wind in urban areas is very difficult because the wind speed is very low. From this problem, this paper presents a windmill using fiberglass. Fiberglass is an alloy or mixture as a composite material which has the characteristics of light weight, easy shape, and low cost. The aim is to analyze the mechanical properties of fiberglass composite materials in the application of blades or vanes in savionus windmills. This study uses the hand lay-up method and the mechanical testing method for tensile strength and impact which aims to determine the material properties of the blade of the savonius windmill. Based on the tensile test, the average tensile strength of random fiberglass composite and 200gr 2-layer woven roving was 49.52 MPa with an average modulus of elasticity of 21.88 Gpa. For the Charphy impact test, the average impact strength is 0.035 joules / mm2 with the energy absorbed is 0.7046 joules.